The Effect of Plyometric Exercise and Arm Muscle Strength on Smash Ability of Pervoba Volleyball Athletes (Journal of Physical Education and Sports, 2019)
Smash is an attack technique to get the point that requires good jumping power and arm muscle strength. This study aimed to analyze the differences in the effect of plyometric depth jump and plyometric split squat jump exercises, find out the difference in the effect between groups having strong arm muscle strength and weak arm muscle strength, and smash ability of pervoba (a name of volleyball team from Banaran, Semarang) volleyball athletes, analyze the interaction of plyometric exercises and arm muscle strength levels on the smash ability. The population in this study was 24 pervoba volleyball athletes aged 20-24 years in which the sample was 20 athletes taken using a purposive sampling technique. This research used a quantitative descriptive method with a 2x2 factorial design. The calculation method in this experimental research used the Statistical Product and Service Solution (SPSS) program. The results of the study: training method had Fvalue = 6.721 > 3.59 with probability of 0.05, arm muscle strength had Fvalue = 3.814 > 3.59 with probability of 0.05, training method and arm muscle strength had Fvalue = 3.723 > 3.59 with probability of 0.05. Eventually, the conclusions of this research are plyometric depth jump training method is better than plyometric split squat jump, athletes having strong arm muscle strength are better than athletes having weak arm muscle strength, there is an interaction between groups using plyometric training method and arm muscle strength on smash ability of pervoba volleyball athletes aged 20-24.